Representation of Mašín brothers as "enemies of socialism" in short stories edited by Naše vojsko publishing house (1966-1987) - Švéda, Josef (Bohemica Olomucensia, 2012)
Short stories about Mašín brothers illustrate the way, how the socialistic state regime tried to get a hegemony and to persuade its citizens arguing that people who did not agree with the system were criminals and murderers.